Propriedades estruturais, vibracionais e morfológicas de microcristais de NaCe(MoO4)2 e nanobastões de h-MoO3 - Moura, João Victor Barbosa (2018)
In this study, we investigated the structural, vibrational and morphological properties of sodium-cerium molybdate microcrystals (NaCe(MoO4)2) and hexagonal molybdenum oxide nanorods (h-MoO3) using X-ray diffraction, Raman and infrared spectroscopy and scanning electron microscopy. The NaCe(MoO4)2 microcrystals and the h-MoO3 nanorods were obtained by conventional hydrothermal synthesis route and by precipitation in acid medium, respectively. A phase transitions study was carried out under extreme conditions of pressure and temperature, as well as the performance evaluation of NaCe(MoO4)2 microcrystals in the removal and degradation of Remazol Brilliant Blue R (RB) and Methylene Blue (MB) under irradiation of visible light. The study of NaCe(MoO4)2 at high temperature revealed an isostructural and reversible phase transformation in 748 K, and suggested a connection between ions distributions and structure stability, indicating a possible mechanism for phase transition. In addition, the use of Raman spectroscopy together with the high-pressure technique showed a pre-amorphization of NaCe(MoO4)2 crystals. These results are very important not only for the application, but also as a contribution to the literature of the micrometric molybdate synthesis with controlled morphology and size. The microcrystals showed favorable performance in the removal and degradation of RB and MB dyes, showing the possibility of applying this material as an environmental remediator. The temperature-dependent Raman spectroscopy in h-MoO3 nanorods confirms a phase transformation at the temperature range 675-690K from the hexagonal phase to the orthorhombic phase. The phase transition was confirmed by SEM images of the samples treated thermally at the phase transition threshold and at the maximum temperature value studied. The Raman spectroscopy study combined with the DFT calculations showed that loss of intercalated species from the inner tunnels of the hexagonal structure leads to loss of stability of the h-MoO3 phase. The effect of laser heat treatment on h-MoO3 nanorods was studied using two different laser-heating routes. The incidence with a gradual increase of the power of the laser leads to a process of annealing and improvement of the thermal contacts between the nanorods. On the other hand, the abrupt incidence of laser energy leads to superheat of the nanorods using relatively low laser power. The MoO3 molecules in the vapor phase at high temperatures condense and crystallize near the crater (formed by the laser spot) in the α-MoO3 and β-MoO3 phases. This result evidences that the laser ablation of the h-MoO3 nanorods can be used as a new strategy to obtain β-MoO3.